SHELVING DI PERPUSTAKAAN SD N 8 BETUNG KABUPATEN BANYUASIN - Nusantara, M. Satrio; Syutaridho, Syutaridho (INCIDENTAL : Journal Of Community Service and Empowerment, 2025)
In this increasingly advanced era, libraries function as essential places for storing information. In general, a library is a learning medium that contains a collection of books and information organized according to a specific system. In Indonesia, libraries are categorized into several types, including school libraries, public libraries, special libraries, and university libraries, each with its own characteristics, functions, and purposes based on the needs of their users. For instance, school libraries are more focused on meeting the needs of students. To maximize its function, a library needs to have the appropriate systems in place, such as the processing of library materials, book arrangement (shelving), and room organization. Shelving, which is the process of arranging books on shelves or cabinets according to specific rules, plays a crucial role in facilitating users, especially students, in finding book collections. With proper and systematic arrangement, shelving can improve the accessibility of library collections. This process becomes the final stage in the processing of library materials and plays a vital role in enhancing the efficiency of book searches at the SDN 8 Betung library, thereby supporting the development of students' reading interest